EKSPERIMENTASI MODEL PEMBELAJARAN THINK TALK WRITE (TTW) DAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BILANGAN DITINJAU DARI KECERDASAN LOGIS MATEMATIS SISWA KELAS VII SMP NEGERI SE-KABUPATEN BLORA - Zuhdha Basofi Nugroho; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to investigate the effect of the learning models on learning achievement viewed from the logical mathematical intelligence of the students. This research was a quasi-experimental research with a 3x3 factorial design. The population of the research was the seven class students of Junior High School at Blora regency on academic year 2014/2015 and the samples were students from SMP Negeri 2 Blora, SMP Negeri 1 Ngawen, and SMP Negeri 1 Japah which was taken by using stratified cluster random sampling technique. The data analysis technique used was unbalanced two ways analysis of variance. Based on the data analysis, it was concluded as follows. 1) TTW with scientific approach gave better achievement than TPS, and classical with scientific approach TPS with scientific approach gave better achievement than classical with scientific approach. 2) The students with high logical matematical intelligence better achievement than the students with medium and low logical matematical intelligence. The students with medium logical matematical intelligence better achievement than the students with low logical matematical intelligence. 3) At the students with high and medium logical matematical intelligence, TTW, TPS, and classical with scientific approach gave the same achievement. At the students with low logical matematical intelligence TTW and TPS with scientific approach gave the same achievement, TTW and TPS with scientific approach gave better achievement than classical scientific learning model. 4) In TTW with scientific approach, students with high and medium logical matematical intelligence had the same achievement, students with medium and low logical matematical intelligence had the same achievement, and students with high logical matematical intelligence had better achievement than students with low logical matematical intelligence. In TPS with scientific approach students with high logical matematical intelligence had better achievement than students with medium and low logical matematical intelligence, and students with medium and low logical matematical intelligence had the same achievement. In classical with scientific approach, students with high and medium logical matematical intelligence had the same achievement, students with high and medium logical matematical intelligence had better achievement than students with low logical matematical intelligence.Keywords: Think Pair Share, Think Talk Write, Classical learning model, Scientific Approach, Logical Matematical Intelligence, Achievement.